Experimental Infection of voles with Francisella tularensis indicates their amplification role in tularemia outbreaks. - Heidi Rossow (Public Library of Science (PLoS), 2014)
Tularemia outbreaks in humans have been linked to fluctuations in rodent population density, but the mode of bacterial maintenance in nature is unclear. Here we report on an experiment to investigate the pathogenesis of Francisella tularensis infection in wild rodents, and thereby assess their potential to spread the bacterium. We infected 20 field voles (Microtus agrestis) and 12 bank voles (Myodes glareolus) with a strain of F. tularensis ssp. holarctica isolated from a human patient. Upon euthanasia or death, voles were necropsied and specimens collected for histological assessment and identification of bacteria by immunohistology and PCR. Bacterial excretion and a rapid lethal clinical course with pathological changes consistent with bacteremia and tissue necrosis were observed in infected animals. The results support a role for voles as an amplification host of F. tularensis, as excreta and, in particular, carcasses with high bacterial burden could serve as a source for environmental contamination.